DOUBLE AXIS MODE OF BATAN’S TRIPLE AXIS SPECTROMETER - Agus Purwanto; Eddy Santoso; Irfan Hafid; M. Refai Muslih (Jurnal Sains Materi Indonesia, 2006)
DOUBLE AXIS MODE OF BATAN’S TRIPLE AXIS SPECTROMETER. Triple Axis Spectrometer (TAS), which is an indispensible tool to microscopically probe inelastic scattering processes in condensed matter, has been installed at the Neutron scattering Laboratory of the R & D Center for Materials Science & Technology, BATAN, since 1992. However, the control and data acquisition system have been nonfunctional since 1996. Following an in-house development of the alternative control and data acquisition hardware last year, TAS started to show the capability and reliability of handling the measurement in the double axis mode. This paper reports a double axis mode control and data acquisition software development which benefits from the hardware development.